Ajaran Tarekat Alawiyah Palembang dan Urgensinya dalam Konteks Kehidupan Kontemporer - Munir, Munir (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
The article seeks to analyze the teachings of the Tarekat Alawiyah in Palembang. The study employs qualitative approach emphasizing descriptive and phenomenological analyses toward the subject of the research, namely the leaders and the followers of this Sufi order. The study finds that the teaching of the Tarekat Alawiyah in Palembang relevantly belongs to the teachings of Ta?awwuf Akhl?q? which put emphasis on the importance of worship, noble manners, shar??ah, and knowledge. This Sufi order practices such number of rituals as recitation of the r?tib, ?awl (commemorating the death of important figures like murshid), mawlid (commemorating the birth of the Prophet Muhammad), and making devotional visit to the tombs of the Muslim clerics and hab??ib (descendants of the Prophet). This tarekat differs from other Sufi orders in a sense that it nullifies the process of bay?ah (taking an oath from new member). The study concludes that the Alawiyah Tarekat seems to be relevantly compatible with the needs of the contemporary society. This is so because this tarekat has practically simple rituals which can be easily performed by its members. This feature attracts even youngsters to join this Sufi order.